STUDY OF LOAD TRANSFER CHARACTERISTICS AND SETTLEMENT SCHEME AGAINST TIME IN SEMI-RIGID INCLUSION (CMC) USING THREE DIMENSION NUMERICAL ANALYSIS - Fahmi Trestyawan, Viqri
Construction above unsupported geotechnical conditions like a soft clay, organic soil, peat, or loose sand are sometimes should be done in a limited time then might causing a problem. Soil improvement that can be used to solve the problem typically done by two type of methods, installing a several pile through the soft soil layer or modification soil layer with implementation of ground improvement to trigger the increasing of the strength of soil in global condition. Controlled Modulus Columns (CMC) is a soil improvement technique by forming a semi-rigid inclusion to increasing the strength of soil in order to prevent the settlement and bearing capacity. Semi-rigid inclusion in CMC is type of columns that installed by drilling a hole using a special auger. The auger can displace the spoil in horizontal direction to the shaft of drill hole. This thesis aims to determine the magnitude of settlement that occurred on the ground treat by CMC for case study in Pemalang – Batang toll road, and the role of granular soil layer known as Load Transfer Platform (LTP) in an effort to transfer the load to the column through arching effect that formed inside the LTP. The used of CMC under embankment not only can decrease the settlement but also increasing the bearing capacity and stabilized the slope of embankment. The result of this study indicated that the used of CMC can decrease the settlement on the ground surface up to 50% from the total settlement that occurred. The used of CMC in consolidation analysis can also decrease the pore water pressure inside the soil, because of the load is no longer held by the soil itself but is partially distributed to the columns. CMC system can also increase the stability, especially the value of safety factors on the slope of the embankment